Blunt neck trauma at a level I trauma centre: six-year retrospective case note review. Issue 11 (14th October 2019) - Zakaria, B A; Muzaffar, J; Orr, L E; Coulson, C J; Sharma, N
Abstract: Background: Blunt neck trauma can cause serious morbidity and mortality rates of up to 40 per cent, but there is a paucity of literature on the topic. Method: A retrospective case note review was performed for all blunt neck trauma cases managed at the Queen Elizabeth Hospital Birmingham between 1st January 2011 and 31st December 2017. Results: Seventeen cases were managed, with no mortality and limited morbidity. Most patients were male (70.6 per cent) and road traffic accidents were the most common cause of injury (41.2 per cent). The median age of patients was 40.6 years (range, 21.5–70.3 years). Multidetector computed tomography angiography of the neck was performed in 9 patients (52.9 per cent) with 'hot' reports made by on-duty radiology staff matching consultant reports in all but 1 case. Six patients underwent operative exploration yielding a negative exploration rate of 33.3 per cent. Imaging reports matched operative findings in 3 cases (60 per cent). Conclusion: Blunt neck trauma is uncommon but usually presents in polytrauma. Imaging has inaccuracies when compared with operative findings, regardless of radiological experience.